Keeping Everyone on Board: Gregory the Great's 'Theory of Iconoclasm'. (28th November 2022) - Crostini, Barbara
Abstract : Pope Gregory the Great (s. 590–604) wrote two letters to Bishop Serenus of Marseilles, reproaching his acts of iconoclasm that had led to schism in his community. These short documents are considered to contain Gregory's theory of art as a book for the illiterate and have been criticized for destroying the aura of sacred art to all subsequent Western developments. Here, I argue that the pope's fundamental contribution is to offer instead a theory of iconoclasm. Relying on previous ideas about the pedagogical and communicative power of art and its ability to reach a larger audience beyond the elite, Gregory defends the rights of the community of 'gentiles and illiterates' who find in portable painted panels an expression of their identity in the church at Marseilles. Serenus's wish to impose a superior orthodoxy on the pious if incorrect habits of his flock cannot justify his resorting to iconoclasm. The pope's vigorous condemnation protects the vulnerable minority and sets an important precedent against any acts of iconoclasm in the West.